2018
DOI: 10.1210/jc.2018-00184
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Dehydroepiandrosterone Sulfate With Cardiometabolic Risk Factors in Prepubertal Children

Abstract: Higher DHEAS is not associated with an increased cardiometabolic risk in prepubertal children. Instead, it may be protective, evidenced by an association with lower LDL cholesterol and LDL/HDL cholesterol ratio. The increased cardiometabolic risk in PA shown in many studies may be due to low birth weight and childhood overweight associated with PA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…However, the data are less uniform in females, with no association (He et al 2018 ) or a positive correlation observed in overweight-obese women (Bann et al 2015 ; De Simone et al 2001 ) and an inverse correlation observed in non-obese postmenopausal women (Casson et al 2010 ). However, DHEA-S appears to play a more significant role in women body composition, both in young females (De Simone et al 2001 ; Mäntyselkä et al 2018 ) and in adult ones (Barrett-Connor and Ferrara 1996 ; De Pergola et al 1994 ). The androgen receptor is expressed widely throughout the AT compartment, indicating that white AT adipocytes may be particularly sensitive to androgens (Newell-Fugate 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the data are less uniform in females, with no association (He et al 2018 ) or a positive correlation observed in overweight-obese women (Bann et al 2015 ; De Simone et al 2001 ) and an inverse correlation observed in non-obese postmenopausal women (Casson et al 2010 ). However, DHEA-S appears to play a more significant role in women body composition, both in young females (De Simone et al 2001 ; Mäntyselkä et al 2018 ) and in adult ones (Barrett-Connor and Ferrara 1996 ; De Pergola et al 1994 ). The androgen receptor is expressed widely throughout the AT compartment, indicating that white AT adipocytes may be particularly sensitive to androgens (Newell-Fugate 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are data suggesting the negative effects of precocious/early adrenarche on future metabolic state, especially in women with a history of PA [ 29 , 30 ]. However, recent studies showed that there is no increased cardiometabolic risk in prepubertal children correlated with higher DHEAS [ 31 ]. In our AP group, the girls were predominant, during the follow-up more than half of them presented either impaired glucose tolerance or insulin resistance, only one had minor hypercholesterolaemia and hypertrigliceridaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Premature adrenarche has been associated with overweight/obesity and adverse glucose and lipid metabolism in both AGA- and SGA-born children [79-81]. Still, a recent study did not find an association between high DHEAS levels and adverse cardiometabolic risk factor levels, except higher BMI SDS, in healthy prepubertal primary school children [82]. Low birth weight was associated with higher circulating DHEAS [44, 83] and epinephrine [83] levels in childhood and birth weight had an inverse association with serum DHEAS levels all the way from SGA to LGA children [84, 85].…”
Section: Introductionmentioning
confidence: 99%